(untitled) (Third Sector Social Economic Review, 2017)
The International Cooperative Alliance’s Statement on the Cooperative Identity defines a cooperative as “an autonomous association of persons united voluntarily to meet their common economic, social, and cultural needs and aspirations through a jointly-owned and democratically-controlled enterprise”. In that respect, cooperative is a business organization owned and operated by a group of individuals for their mutual benefit. Members have a close relationship with the enterprise as producers or consumers of its products or services, or as its employees. Addressing these relationships within the perspective of corporate governance principles and application of modern auditing techniques become important to ensure transparency for cooperative societies. Basically, cooperative auditing focuses on cooperative societies and the assessment of every work within the limits of the law signal an important task regarding the knowledge of employees and directors. The audit of a cooperative society is different from that of a limited liability company (company) because the objects and business processes of a cooperative society are quite different from those of a company. This research aims to analyze key issues on governance and auditing for cooperatives to demonstrate the importance of auditing for cooperatives based on international standards. Also policy recommendations are made for best practices of cooperative auditing.